Tree-ring reconstruction of the level of Great Salt Lake, USA. (July 2014) - DeRose, R Justin; Wang, Shih-Yu; Buckley, Brendan M; Bekker, Matthew F
Utah's Great Salt Lake (GSL) is a closed-basin remnant of the larger Pleistocene-age Lake Bonneville. The modern instrumental record of the GSL-level (i.e. elevation) change is strongly modulated by Pacific Ocean coupled ocean/atmospheric oscillations at low frequency, and therefore reflects the decadal-scale wet/dry cycles that characterize the region. A within-basin network of seven tree-ring chronologies was developed to reconstruct the GSL water year (September–August) level, based upon the instrumental record of GSL level from 1876 to 2005. The result was a 576-year reconstruction of the GSL level that extends from 1429 to 2005; all calibration-verification tests commonly used in dendroclimatology were passed. The reconstruction explains 48% of the variance in the instrumental GSL level and exhibits significant periodicity at sub-decadal scales over the past six centuries. Meanwhile, predominance of multi-decadal periodicity in the early half of the record shifted to quasi-decadal dominance in the latter half, and this is consistent with that of proxy reconstructions of the Pacific Decadal Oscillation. The GSL-level reconstruction is a crucial component to improving our insight into the possible controls of coupled ocean-atmosphere interactions on precipitation delivery.